Gender vulnerability assessment to inform gender-sensitive adaptation action: a case study in semi-arid areas of Mali - Segnon, Alcade C.; Magassa, Mariame; Obossou, Esdras Abréwa Rêmilokoun; Partey, Samuel T.; Houessionon, Prosper; Zougmoré, Robert B. (Frontiers in Climate, 2024)
Understanding the gender dimensions of vulnerability to climate change is crucial for designing effective gender-transformative climate actions. This is particularly crucial in the semi-arid regions of West Africa, a climate change “hotspot” where high dependence on climate-sensitive livelihoods and limited adaptive capacity make agriculture and livelihoods highly vulnerable. In this study we combined semi-structured interviews and focus group discussions with a systematic literature review to analyze gendered household vulnerability to climate change in Cinzana, a semi-arid area of Mali, and identify entry points for gender-transformative adaptation actions. The Livelihood Vulnerability assessment indicated that female-headed households were more vulnerable than male-headed households. Differential socio-demographic profiles, livelihood strategies, social networks, water and food and agricultural production systems were key drivers of the gendered vulnerability patterns. A systematic review of drivers of gendered vulnerability in Mali illustrated how socio-cultural norms and roles assigned to women, and limited women access to and control over productive resources and adaptation technologies make women more vulnerable to climatic and non-climatic risks. We highlight the need of gender transformative approaches to address the structural gender inequality and reduce vulnerability of female-headed households. We outline three pathways for reducing female-headed households’ vulnerability to climate change, including the promotion of gender-smart extension and climate advisory services and empowering women.